PENYAMPAIAN KELUHAN KONSUMEN SURABAYA DI HOTEL BINTANG LIMA - Yansi Dwi Anggriana; Nicolas Krisianto A.P; Adriana Aprilia (Journal of Tourism Destination and Attraction, 2019)
Abstract: Tourism is one of many business that developed as time goes by. Many hotels have been built not only in a big city but also in a small city. Hotel which have many kind of variation and stars can influence consumer’s expectation. Higher expectation tend to be more difficult to fulfilled. When a hotel failed to meet up to that expectation, then it can cause consumer to make a complaint. This study intended to knowing the segmentation of Surabaya’s consumer who made a complaint in a five stars hotel in terms of demographic, culture, and character. Method of data processing is done by using validity and reliability tests. Meanwhile data analysis method that used in this research is the analysis factor and cluster analysis, which were derived from data collected from the questionnaire that has been filled out and processed. Through these datas, turn out 12 factors and 3 cluster with the majority cluster from Surabaya’s consumer is inertia. Keyword : Complaint, consumer, cluster